Differences in transcript levels of ABC transporters between pancreatic adenocarcinoma and nonneoplastic tissues - Mohelnikova-Duchonova, Beatrice; Brynychova, Veronika; Oliverius, Martin; Honsova, Eva; Kala, Zdenek; Muckova, Katarina; Soucek, Pavel (Pancreas, 2013)
OBJECTIVES: The aim of this study was to evaluate transcript levels of all 49 human ATP-binding cassette transporters (ABCs) in one of the most drug-resistant cancers, namely, the pancreatic ductal adenocarcinoma (PDAC). Association of ABCs levels with clinical-pathologic characteristics and KRAS mutation status was followed as well. METHODS: Tumors and adjacent nonneoplastic tissues were obtained from 32 histologically verified PDAC patients. The transcript profile of ABCs was assessed using quantitative real-time polymerase chain reaction with a relative standard curve. KRAS mutations in exon 2 were assessed by high-resolution melting analysis and sequencing. RESULTS: Most ABCs were deregulated in PDAC and 10 ABCs were associated with clinical-pathologic characteristics. KRAS mutations did not change the global expression profile of ABCs. CONCLUSIONS: The expression of ABC transporters was significantly deregulated in PDAC tumors when compared to nonmalignant tissues. The observed up-regulation of ABCB4, ABCB11, ABCC1, ABCC3, ABCC5, ABCC10, and ABCG2 in tumors may contribute to the generally poor treatment response of PDAC. The up-regulation of ABCA1, ABCA7, and ABCG1 implicates a serious impairment of cellular cholesterol homeostasis in PDAC. On the other hand, the observed down-regulation of ABCA3, ABCC6, ABCC7, and ABCC8 suggests a possible role of stem cells in the development and progression of PDAC.
Keywords: duktální karcinom slinivky břišní; exprese genu; protoonkogenní proteiny p21(ras); Gene Expression; RNA, Messenger; Male; mutace; pankreas; Proto-Oncogene Proteins; Carcinoma, Pancreatic Ductal; chemorezistence; Ras proteiny; Aged; Pancreas; mužské pohlaví; senioři; lidé středního věku; Pancreatic Neoplasms; RNA nádorová; senioři nad 80 let; lidé; ženské pohlaví; RNA, Neoplasm; Humans; nádory slinivky břišní; Aged, 80 and over; Proto-Oncogene Proteins p21(ras); Drug Resistance, Neoplasm; ABC transportéry; Mutation; ras Proteins; Female; messenger RNA; protoonkogenní proteiny; Middle Aged; ATP-Binding Cassette Transporters